Response to 5-Fluorouracil-Based Chemotherapy in a Patient with Metastatic Colonic-Type Adenocarcinoma Arising in a Primary Mediastinal Teratoma - Arunee Dechaphunkul; Gilbert Bigras; Michael Sawyer (Case Reports in Oncological Medicine)
Germ cell tumor with somatic malignant transformation is an uncommon phenomenon occurring about 7% of all mediastinal teratomas. Among all transformed component, sarcoma appears to be the most frequent histology, followed by primitive neuroectodermal tumor (PNET) and adenocarcinoma. To our knowledge, there were 3 cases of colonic-type adenocarcinoma arising in a primary teratoma have been reported to date. However, none of them received chemotherapy directed to transformed histology given localized disease at presentation. We, therefore, report here the first case of patient who achieved good response from chemotherapy directed to transformed histology, which confirms the importance of chemotherapy regimen used.